PENGARUH JARAK SWIRL FAN TERHADAP LAJU PENURUNAN TEMPERATUR CASE, HAMBATAN TERMAL DAN EFEKTIFITAS FIN PADA EXTRUDE FIN - Atmadja, Sugeng Tirta (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2006)
In the electronical series, the cooling upon electronical component is highly required. In this final assignment, the writer discusses about the effect of cooling using swirl fan effect with distance variation which is usually called as a wind flow effect. This effect is obtained from the fluids flow turned by a fan, in which the direction of fluids flow is spreed by fan located between the source of flow and cooled component. By using swirl fan effect which its distance is modified, it is expected to increase turbulence effect of fluids flow and recognize the most optimum distance that will effect to the flow of air cooling. The used distance variation are 1cm, 3cm, 5cm, 7cm, 9cm and 11cm. By using the method, the fast heat cooling is generated. The standard of swirl fan effect using is by not using swirl fan, so that the flow is just let without any obstacles. The existing result indicated that the using of swirl fan effect on the distance of 3cm is more optimum than on the other distance and it is better than the one wich does not use swirl fan. In the speed of 6,6 m/s for all variation, the power generates smaller thermal resistance than the speed of 2,8 m/s and 4,3 m/s and the effectivity in the condition without swirl fan is better than the fin using swirl fan for both kinds of heat sink